Alkaline zinc-manganese battery positive electrode and preparation method thereof
Patent Information
- Application Number
- CN202411909263.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to an alkaline zinc-manganese battery positive electrode and a preparation method thereof. Background Art
[0002] As a traditional energy storage element, the basic structure of primary alkaline zinc-manganese battery is divided into positive electrode, negative electrode, separator, electrolyte, positive electrode collector and external steel shell. The capacity of alkaline manganese battery is usually limited by the positive electrode, which is mainly composed of electrolytic manganese dioxide, conductive agent, binder and other materials. Among them, electrolytic manganese dioxide is the active material with low intrinsic conductivity (10 -3 ~10 -5 S / cm), so it is necessary to match a conductive agent with excellent conductivity to enhance its conductivity. At present, the conductive agent used in the positive electrode of alkaline manganese battery is usually: conductive graphite.
[0003] Alkaline manganese battery industry workers have been pursuing higher battery discharge performance, mainly through technological innovation and material improvement to achieve this goal. Chinese patent CN109841834A discloses a composite conductive agent for lithium-ion batteries, which improves the conductivity of the positive electrode of lithium-ion batteries by combining acetylene black, conductive graphite, nano-carbon fiber, carbon nanotubes and graphene. Chinese patent CN114695895A discloses the addition of carbon nanotubes, graphene and other conductive agents with better conductivity into the conductive agent of the positive electrode of lithium-manganese button batteries to enhance the battery discharge performance of lithium-manganese button batteries. However, no matter what type of battery (including primary alkaline zinc-manganese batteries), there is still room for improvement and optimization of the electrical performance.
[0004] In addition, graphene has a large specific surface area (BET: 20-35 m 2 = / g), which is easy to agglomerate together, not only reducing its own adsorption capacity but also affecting the excellent performance of graphene itself. In order to make the graphene dispersed evenly, the Chinese patent of CN109841834A pre-dissolves graphene, nano carbon fiber and carbon nanotube in NMP organic solvent and performs wet mixing to obtain a uniformly dispersed conductive slurry. Since the positive electrode process of a primary alkaline zinc-manganese battery requires that the positive electrode mixed powder has a high solid content level of 97%, so as to facilitate the normal progress of the subsequent granulation and tableting processes, the graphene slurry dispersion process of CN109841834A cannot be applied in a primary alkaline zinc-manganese battery. In addition, the Chinese patent of CN114695895A pre-disperses graphene, nano carbon fiber and carbon nanotube in an aqueous solution, and then wet mixes with positive electrode powders such as manganese dioxide, and finally needs to vacuum dry the positive electrode mixture to remove excess water. This method requires additional vacuum drying process and vacuum drying equipment. Summary of the invention
[0005] The first object of the present invention is to provide an alkaline zinc-manganese battery positive electrode, which uses the specific surface area ratio between the conductive agent and the electrolytic manganese dioxide and the total conductivity of the conductive agent and the electrolytic manganese dioxide as screening conditions to determine the alkaline zinc-manganese battery formula corresponding to good battery performance, thereby achieving more precise control of the content of the conductive agent and the electrolytic manganese dioxide in the alkaline zinc-manganese battery formula, which is conducive to further improving the battery performance.
[0006] A positive electrode for an alkaline zinc-manganese battery comprises electrolytic manganese dioxide and a conductive agent, wherein the conductive agent comprises graphene; the addition ratio of the conductive agent to the electrolytic manganese dioxide is 2.95-4:96-97.05, and the following two conditions are satisfied at the same time: the total surface area of the conductive agent / the total surface area of the electrolytic manganese dioxide=0.025-0.037 and the total conductivity of the conductive agent and the electrolytic manganese dioxide is ≥1.5S / cm.
[0007] In the prior art, the appropriateness of the amount of conductive agent is usually evaluated directly based on the battery discharge performance index to screen the appropriate conductive agent formula and amount, which ignores the fundamental factors affecting battery performance and the screening results are not accurate enough.
[0008] The inventors have studied the positive electrode reaction mechanism of primary alkaline zinc-manganese battery MnO2+H2O+e - —MnOOH +Starting from the positive electrode reaction, considering that the electrons need to enter the manganese dioxide lattice from the interface between the electrolytic manganese dioxide and the conductive agent to the position of manganese in the reaction process of the positive electrode, there are two core conditions for good battery performance: first, the manganese dioxide and the conductive agent must have a sufficiently high conductivity; second, there must be a sufficiently large contact area between the manganese dioxide and the conductive agent. The matching relationship between the specific surface area of manganese dioxide and the conductive agent and the corresponding total conductivity of the two will change with the changes in the type and proportion of the conductive agent and the proportion of electrolytic manganese dioxide. Therefore, the inventors mixed the conductive agent and electrolytic manganese dioxide evenly to obtain a composite powder, studied the relationship between the surface area ratio of the conductive agent and electrolytic manganese dioxide, the conductivity of the composite powder (i.e., the total conductivity of the conductive agent and electrolytic manganese dioxide), and the battery performance, and used "the total surface area of the conductive agent / the total surface area of electrolytic manganese dioxide = 0.025-0.037" and "the total conductivity of the conductive agent and the electrolytic manganese dioxide ≥ 1.5S / cm" as screening conditions to determine the alkaline zinc-manganese battery formula corresponding to good battery performance. Since both "the total surface area of the conductive agent / the total surface area of electrolytic manganese dioxide" and "the total conductivity of the conductive agent and the electrolytic manganese dioxide" are jointly determined by the composition formula of the conductive agent and the amount of the conductive agent, it is possible to achieve more accurate regulation of the content of the conductive agent and electrolytic manganese dioxide in the alkaline zinc-manganese battery formula. In addition, the research results found that: when the above-mentioned screening conditions are met, the corresponding ratio of the conductive agent to electrolytic manganese dioxide can reach less than 4:96 (specifically: 2.95~4:96~97.05), which can maximize the use of electrolytic manganese dioxide. While the energy density of the battery at low current is improved, the rate performance of the battery at medium and large currents also shows a significant improvement.
[0009] Furthermore, the alkaline zinc-manganese battery positive electrode also includes potassium hydroxide electrolyte and a binder, wherein the potassium hydroxide electrolyte is 1-3% and the binder is 0.1-0.6%.
[0010] Furthermore, the conductive agent also includes conductive graphite, and the conductive graphite is flake graphite and / or expanded graphite. Wherein, the content of graphene in the conductive agent is preferably controlled at 10-60%. Furthermore, the conductive agent is composed of flake graphite, expanded graphite and graphene, wherein flake graphite is 20-50%, expanded graphite is 30-70%, and graphene is 10-30%.
[0011] Furthermore, the graphene is selected to have a specific surface area of ≥20m 2 / g of graphene. Using graphene with a relatively large specific surface area is conducive to reducing the amount of graphene added and the amount of composite conductive agent added. The microstructure of the graphene can be multi-layer or single-layer.
[0012] The second object of the present invention is to provide a process for preparing the positive electrode of the alkaline zinc-manganese battery, comprising the following steps: (1) Solid phase dispersion step of the two-step method; ① High-speed solid phase dispersion: The conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are pre-dispersed uniformly by high-speed stirring, with a dispersion line speed of 8m / s≤≤12m / s, and a dispersion time of 10min≤≤30min, to obtain a composite conductive agent powder; ② Low-speed solid phase dispersion: Add electrolytic manganese dioxide to the composite conductive agent powder obtained in the high-speed solid phase dispersion step and disperse it evenly at a low speed, with a dispersion linear speed of 2m / s≤≤4m / s, and a dispersion time of 10min≤≤20min, to obtain a positive electrode powder; (2) Spraying potassium hydroxide electrolyte into the positive electrode powder obtained in step (1), and performing wet mixing to obtain a positive electrode mixture for an alkaline zinc-manganese battery.
[0013] Since the density of graphene is 0.05-0.1g / ml, the density of flake graphite and expanded graphite is 0.06-0.15g / ml, and the density of electrolytic manganese dioxide is 1.6-1.8g / ml, the density difference between graphene and manganese dioxide is very large. If the two are directly dispersed, due to the density difference, graphene is easy to be on the upper layer and manganese dioxide is easy to sink, causing graphene to easily agglomerate together, making it more difficult to disperse graphene and reducing efficiency. However, the density difference between graphene and conductive graphite is not too large, and there is no unevenness caused by density difference. Therefore, the two-step solid phase dispersion process adopted by the present invention first mixes the conductive graphite and graphene, and utilizes the rigid friction of the conductive graphite (flake graphite and expanded graphite) combined with a high high-speed dispersion line speed to achieve efficient dispersion of the graphene powder; because the graphene has been dispersed in the first high-speed solid phase dispersion step, the mixing efficiency of the second low-speed solid phase dispersion step and manganese dioxide is easy, and a more efficient dispersion efficiency can be achieved relative to directly dispersing the graphene and manganese dioxide. During the low-speed solid phase dispersion, the dispersion line speed is reduced to avoid excessive dispersion line speed, which will have a certain impact on the particle size and bound water content of manganese dioxide, thereby affecting battery performance. DETAILED DESCRIPTION
[0014] The preferred embodiments of the alkaline zinc-manganese battery positive electrode and the preparation method thereof of the present invention are described in detail below.
[0015] A positive electrode for an alkaline zinc-manganese battery comprises electrolytic manganese dioxide and a conductive agent, wherein the conductive agent comprises graphene; the addition ratio of the conductive agent to the electrolytic manganese dioxide is 2.95-4:96-97.05, and the following two conditions are satisfied at the same time: the total specific surface area of the conductive agent / the specific surface area of the electrolytic manganese dioxide=0.025-0.037 and the total conductivity of the composite conductive agent and the electrolytic manganese dioxide is ≥1.5S / cm.
[0016] During the experimental stage, the inventors combined the conductive agents and electrolytic manganese dioxide of different formulations according to the composition of the conductive agent in Table 1 (the content of the conductive agent ranged from 2.95 to 4%), and mixed them according to the conventional stirring and mixing process (line speed of 1 to 2 m / s) to obtain a composite powder. During the mixing process, samples were taken at intervals of a certain period of time to test the carbon content at different positions to determine the uniformity of the mixing, and the mixing time (i.e., dispersion time) required for uniform mixing was recorded. The specific surface area (BET) of electrolytic manganese dioxide and the specific surface area (BET) of various conductive agents were tested by a dynamic method, and the ratio of the total surface area of electrolytic manganese dioxide to the total surface area of the conductive agent was calculated with reference to the amount in the battery. Take the composite powder and test its conductivity.
[0017] Table 1
[0018] From the test results in Table 1, it can be seen that when the ratio of the total surface area of the conductive agent to the total surface area of the electrolytic manganese dioxide is between 0.025 and 0.037, and the total conductivity of the conductive agent and the electrolytic manganese dioxide is ≥1.5S / cm, the corresponding addition ratio of the conductive agent to the electrolytic manganese dioxide is 2.95-4:96-97.05. Compared with the current conductive agent addition ratio in traditional alkaline zinc-manganese batteries, the proportion of the conductive agent is lower, and at the same time, the proportion of electrolytic manganese dioxide is higher, which is conducive to improving battery performance. In addition, due to the addition of graphene in the conductive agent, the traditional mixing process of alkaline manganese batteries requires a longer dispersion time, and the efficiency of uniform mixing decreases significantly. Moreover, as the proportion of graphene added increases, the time to achieve uniform mixing becomes longer.
[0019] Add 0.4% of binder to the above-mentioned uniformly mixed composite powder, mix well, spray potassium hydroxide electrolyte, wet mix well, roll, granulate, sieve, press into positive electrode ring of alkaline manganese battery LR6, and assemble into LR6 alkaline manganese battery. After standing for 1 week at room temperature 20±2℃, test the electrical performance, test the internal resistance of the battery, and select large, medium and small current modes to test the electrical performance of the battery. Comparative Example 1 is taken as 100% for discharge performance.
[0020] Table 2
[0021] From the test results in Table 2, with the addition of graphene materials, the internal resistance of the battery is relatively reduced to varying degrees; moreover, the discharge performance of the battery under small, medium and large currents (performance improvement, uniformity of discharge performance) is closely related to the total surface area ratio of the conductive agent to the electrolytic manganese dioxide and the conductivity of the composite powder. When the total surface area ratio of the conductive agent to the electrolytic manganese dioxide is too low (Comparative Example 1 to Comparative Example 7), the uniformity of the battery under large current discharge is not ideal (lower than 90%), which is speculated to be caused by insufficient conductive agent area and insufficient consistency of the conductive network. Ensure that the total surface area of the conductive agent / total surface area of the active material electrolytic manganese dioxide meets the requirements of the present invention, reduce the amount of the conductive agent, increase the ratio of the active material electrolytic manganese dioxide (the ratio of the conductive agent to manganese dioxide in the present invention can be reduced to a minimum of 2.95:97.05), the discharge uniformity of the battery under each current mode is maintained at a level above 95%, and the performance is significantly improved at the large, medium and small current densities evaluated. When the total surface area ratio of the conductive agent to electrolytic manganese dioxide is greater than 0.037 (Comparative Example 8), although the conductivity is also very high, the discharge performance under large and small currents does not increase, and the discharge performance under medium current is reduced to a certain extent. In addition, the proportion of graphene in the conductive agent increases, which prolongs the dispersion time. At the same time, the uniformity of battery performance is relatively poor. When the ratio of the conductive agent to electrolytic manganese dioxide exceeds 4:96 (Comparative Example 9), due to the decrease in the proportion of active material manganese dioxide, all performances show a certain decrease, especially the small current performance, which decreases significantly.
[0022] In addition, it can be seen from the above examples and comparative examples that the addition of graphene, using a conventional mixing process (line speed of 2 m / s), requires a relatively long mixing time, which significantly reduces the mixing efficiency. Moreover, the higher the proportion of graphene, the greater the difficulty of mixing.
[0023] The inventors also prepared composite powders according to the composite conductive agent formula of "expanded graphite 60% / graphene 40%" (the same as the above-mentioned Example 10) by using a two-step solid phase dispersion step. The two-step solid phase dispersion step is: ① High-speed solid phase dispersion: Graphene and expanded graphite are pre-dispersed uniformly by high-speed stirring to obtain composite conductive agent powder; ② Low-speed solid phase dispersion: electrolytic manganese dioxide is added to the composite conductive agent powder obtained in the high-speed solid phase dispersion step for low-speed uniform dispersion at a dispersion linear velocity of 2 m / s to obtain positive electrode powder (ie, the composite powder).
[0024] The dispersion time required to achieve uniform mixing of the composite conductive agent powder at different line speeds was recorded (see Table 3 below). In addition, the change in the average particle size of the composite conductive agent powder after dispersion at different line speeds was used to determine whether the line speed would damage the physical properties of the conductive powder.
[0025] Table 3
[0026] From the test results in Table 3, it can be seen that as the line speed increases, the dispersion time will be greatly reduced. The line speed of high-speed solid phase dispersion increases from 12m / s to 15m / s, and the dispersion efficiency is not significantly affected. In addition, from the test of the particle size of the conductive agent after dispersion, after the line speed is increased to 15m / s, the particle size of the composite conductive agent powder decreases significantly, and it is believed that it has a certain destructive effect on the particles of conductive graphite. Therefore, the dispersion line speed is preferably controlled at 12-15m / s during solid phase dispersion. At this time, the dispersion time of high-speed solid phase dispersion is only 15min, which is much shorter than the dispersion time (60min) at the conventional dispersion line speed (1-2m / s), and the dispersion efficiency is significantly improved.
[0027] Therefore, the preparation process of the positive electrode of the alkaline zinc-manganese battery of the present invention comprises the following steps: (1) Solid phase dispersion step of the two-step method; ① High-speed solid phase dispersion: The composite conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are pre-dispersed uniformly by high-speed stirring, with a dispersion line speed of 8m / s≤≤12m / s, and a dispersion time of 10min≤≤30min, to obtain a composite conductive agent powder; ② Low-speed solid phase dispersion: Add electrolytic manganese dioxide to the composite conductive agent powder obtained in the high-speed solid phase dispersion step and disperse it evenly at a low speed, with a dispersion linear speed of 2m / s≤≤4m / s, and a dispersion time of 10min≤≤20min, to obtain a positive electrode powder; (2) Spraying potassium hydroxide electrolyte into the positive electrode powder obtained in step (1), and performing wet mixing to obtain a positive electrode mixture for an alkaline zinc-manganese battery.
[0028] Generally speaking, the potassium hydroxide electrolyte in the alkaline zinc-manganese battery positive electrode is controlled at 1-3%, and the binder is controlled at 0.1-0.6%. The binder can be added together with electrolytic manganese dioxide in step ②, or added to the positive electrode powder after step ②.
[0029] The conductive agent may be entirely graphene, or may be a composite conductive agent consisting of graphene and conductive graphite. The conductive graphite may be flake graphite and / or expanded graphite.
[0030] When the conductive graphite is composed of flake graphite and expanded graphite, the composite conductive agent contains 20-70% flake graphite, 20-90% expanded graphite, and 10-60% graphene.
[0031] Preferably, the graphene has a specific surface area of ≥ 20 m 2 / g of graphene. Using graphene with a relatively large specific surface area is conducive to reducing the amount of graphene added and the amount of composite conductive agent added. The microstructure of the graphene can be multi-layer or single-layer.
[0032] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An alkaline zinc-manganese battery positive electrode, comprising electrolytic manganese dioxide and a conductive agent, characterized in that: The conductive agent includes graphene; the addition ratio of the conductive agent to electrolytic manganese dioxide is 2.95-4:96-97.05, and the following two conditions are met at the same time: the total surface area of the conductive agent / the total surface area of the electrolytic manganese dioxide=0.025-0.037 and the total conductivity of the conductive agent and the electrolytic manganese dioxide is ≥1.5S / cm.
2. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The alkaline zinc-manganese battery positive electrode also includes potassium hydroxide electrolyte and binder, wherein the potassium hydroxide electrolyte is 1-3% and the binder is 0.1-0.6%.
3. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The conductive agent further comprises conductive graphite, and the conductive graphite is flake graphite and / or expanded graphite.
4. The alkaline zinc-manganese battery positive electrode according to claim 3, characterized in that: The content of graphene in the conductive agent is controlled at 10-60%.
5. The alkaline zinc-manganese battery positive electrode according to claim 3, characterized in that: The conductive agent is composed of flake graphite, expanded graphite and graphene, wherein the flake graphite accounts for 20-50%, the expanded graphite accounts for 30-70% and the graphene accounts for 10-30%.
6. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The graphene has a specific surface area of ≥20m 2 / g of graphene.
7. The process for preparing the positive electrode of the alkaline zinc-manganese battery as claimed in claim 1, comprising the following steps: (1) Solid phase dispersion step of the two-step method; ① High-speed solid phase dispersion: The conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are pre-dispersed uniformly by high-speed stirring, with a dispersion line speed of 8m / s≤≤12m / s, and a dispersion time of 10min≤≤30min, to obtain a composite conductive agent powder; ② Low-speed solid phase dispersion: Add the electrolytic manganese dioxide to the composite conductive agent powder obtained in the high-speed solid phase dispersion step and disperse it evenly at a low speed, with a dispersion linear speed of 2m / s≤≤4m / s, and a dispersion time of 10min≤≤20min, to obtain a positive electrode powder; (2) Spraying potassium hydroxide electrolyte into the positive electrode powder obtained in step (1), and performing wet mixing to obtain a positive electrode mixture for an alkaline zinc-manganese battery.
Citation Information
Patent Citations
Composite conductive agent, preparation method thereof and application of composite conductive agent in positive electrode slurry
CN109841834A
Lithium-manganese button cell positive electrode material doped with graphene, preparation method and application
CN114695895A
Alkaline battery
CN104218228A
Primary alkaline battery with integrated in-cell resistances
CN106687815A
Preparation device and preparation method of alkaline battery positive electrode
CN113964286A